Infection-activated lipopeptide nanotherapeutics with adaptable geometrical morphology for in vivo bacterial ablation. (December 2022) - Yu, Qi-Hang; Huang, Rong; Wu, Kai-Yue; Han, Xiao-Le; Cheng, Yin-Jia; Liu, Wen-Long; Zhang, Ai-Qing; Qin, Si-Yong
Abstract: The nonselective membrane disruption of antimicrobial peptides (AMPs) helps in combating the antibacterial resistance. But their overall positive charges lead to undesirable hemolysis and toxicity toward normal living cells, as well as the rapid clearance from blood circulation. In consequence, developing smart AMPs to optimize the antimicrobial outcomes is highly urgent. Relying on the local acidity of microbial infection sites, in this work, we designed an acidity-triggered charge reversal nanotherapeutics with adaptable geometrical morphology for bacterial targeting and optimized therapy. C16 -A3 K4 -CONH2 was proposed and the ε-amino groups in lysine residues were acylated by dimethylmaleic amide (DMA), enabling the generated C16 -A3 K4 (DMA)-CONH2 to self-assemble into negatively charged spherical nanostructure, which relieved the protein adsorption and prolonged blood circulation in vivo . After the access of C16 -A3 K4 (DMA)-CONH2 into the microbial infection sites, acid-sensitive β-carboxylic amide would hydrolyze to regenerate the positive C16 -A3 K4 -CONH2 to destabilize the negatively charged bacterial membrane. In the meanwhile, attractively, the self-assembled spherical nanoparticle transformed to rod-like nanostructure, which was in favor of the efficient binding with bacterial membranes due to the larger contact area. Our results showed that the acid-activated AMP nanotherapeutics exhibited strong and broad-spectrum antimicrobial activities against Yeast, Gram-positive Staphylococcus aureus, Gram-negative Escherichia coli, and methicillin-resistant Staphylococcus aureus (MRSA). Moreover, the biocompatible lipopeptide nanotherapeutics dramatically improved the dermapostasis caused by bacterial infection. The strategy of merging pathology-activated therapeutic function and morphological adaptation to augment therapeutic outcomes shows the great potential for bacterial inhibition. Statement of significance: The overall positive charges of antimicrobial peptides (AMPs) lead to undesirable hemolysis and nonselective toxicity, as well as the rapid clearance from blood circulation. Infection-activated lipopeptide nanotherapeutics with adaptable geometrical morphology were developed to address these issues. The self-assembled lipopeptide was pre-decorated to reverse the positive charge to reduce the hemolysis and nonselective cytotoxicity. After accessing the acidic infection sites, the nanotherapeutics recovered the positive charge to destabilize negatively charged bacterial membranes. Meanwhile, the morphology of self-assembled nanotherapeutics transformed from spherical nanoparticles to rod-like nanostructures in the lesion site, facilitating the improved association with bacterial membranes to boost the therapeutic efficiency. These results provide new design rationale for AMPs developed for bacterial inhibition. Graphical abstract: Image, graphical abstract